Do soil biota influence the outcome of novel interactions between plant competitors?. (13th August 2018) - Cardinaux, Aline; Hart, Simon P.; Alexander, Jake M.
Abstract: Species are shifting their ranges, for example to higher elevations, in response to climate change. Different plant species and soil microbiota will likely shift their ranges at different rates, giving rise to novel communities of plants and soil organisms. However, the ecological consequences of such novel plant–soil interactions are poorly understood. We experimentally simulated scenarios for novel interactions arising between high‐ and low‐elevation plants and soil biota following asynchronous climate change range shifts, asking to what extent the ability of plants to coexist depends on the origin of the soil biota. In a greenhouse experiment, we grew pairs of low‐ ( Poa trivialis and Plantago lanceolata ) and high‐ ( Poa alpina and Plantago alpina ) elevation plant species alone and against a density gradient of con‐ or heterospecific neighbours. Plants grew on sterilized field soil that was inoculated with a soil community sampled from either low or high elevation in the western Swiss Alps. We used the experiment to parameterize competition models, from which we predicted the population‐level outcomes of competition in the presence of the different soil biota. In the absence of neighbours, three of the four species produced more biomass with the low‐elevation soil biota. As a result of generally similar responses across plant species, soil biota tended not to affect plant interaction outcomes, with the low‐elevation species generally predicted to competitively exclude high‐elevation species irrespective of the soil biota origin. However, the low‐elevation grass Poa trivialis was only able to invade communities of Poa alpina in the presence of a low‐elevation soil biota. This suggests that, at least in some cases, the outcome of novel competitive interactions between plants following climate change will depend on whether shifts in the distribution of plants and soil organisms are asynchronous. Synthesis . Our results indicate that the changing soil communities that plants encounter during range expansion can influence plant performance. However, this is only likely to alter expectations for the ability of plants to coexist following climate change if plant species respond differently to the change in the soil community. Abstract : Our results indicate that the changing soil communities that plants encounter during range expansion can influence plant performance. However, this is only likely to alter expectations for the ability of plants to coexist following climate change if plant species respond differently to the change in the soil community.